Investigation into the changes in blood parameters in Acanthobrama marmid Heckel, 1843 living in Keban Dam Lake - Basusta, AG; Sen, D (Scientific Technical Research Council Turkey, 2004)
In this study, 212 Acanthobrama marmid Heckel, 1843 individuals were caught at monthly periods from Keban Dam Lake between January 1997 and December 1998 and transported live to the laboratory. After haematological analysis was carried out on the blood samples taken from their hearts, total lengths and weights were measured. The sex of the fish was identified and their ages were determined from the scales. The total amounts of erythrocytes, leucocytes, thrombocytes, haemoglobin and haematocrits and MCV, MCH and MCHC parameters were determined from blood samples. The formulae of leucocytes were examined from blood preparations of each sample. The distributions of blood parameters with respect to age, length and weight groups, sex of fish, month and season were also examined.
Keban baraj gölü'nde yaşayan Acanthobrama marmid Heckel, 1843'de kan Parametrelerinin İncelenmesi
Keywords: Acanthobrama marmid; blood parameters; age determination; sex; Keban Dam Lake